Determinants of child malnutrition in Bangladesh - A Multivariate Approach - Fazle Rabbi, Ahbab Mohammad; Karmaker, Shamal Chandra (Asian Journal of Medical Sciences, 2014)
Objective: Malnutrition is referred as the greatest single threat to the world’s public health, especially for the developing countries. Nutritional status is determined anthropometrically and it is outcome of complex interactions between biological, socio-economical variables. This study is conducted to identify the significant determinants of child malnutrition in Bangladesh. Method: Using BDHS-2007 data, Total 5312 cases are included in the present study. Multivariate techniques have been applied in this study to obtain significant determinants of child malnutrition. Results: Factor analysis revealed six factors as covariate of malnutrition; where two factors are socio-economical, others are biological and bio-social. Hence linear discriminant analysis is used to clarify the efficiency of obtained factors in malnutrition scenario; which imply that the obtained factors are accurate for approximately 60 percent observations. Conclusion: The obtained results suggest that, consciousness should be raised to improve socio-economic and maternal health conditions to improve the scenario of child malnutrition. DOI: http://dx.doi.org/10.3126/ajms.v6i2.10404 Asian Journal of Medical Sciences Vol.6(2) 2015 85-89